Determinant of Employee Engagement and Productivity: An Analysis of Work Motivation, Competence - Agustian Zen (PT FORMOSA CENDEKIA GLOBAL, 2023)
It shows that the variables in the field of human resources offered in this scientific article reinforce through the existing literature review, by looking at and being stretched as in result of the author's perspective. An ascientific article is that it can be continued in this variable can be used by other researchers together into one variable in a research result.